2016
DOI: 10.1016/j.tplants.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Decision Support Tools for Genomics-Assisted Breeding

Abstract: To successfully implement genomics-assisted breeding (GAB) in crop improvement programs, efficient and effective analytical and decision support tools (ADSTs) are 'must haves' to evaluate and select plants for developing next-generation crops. Here we review the applications and deployment of appropriate ADSTs for GAB, in the context of next-generation sequencing (NGS), an emerging source of massive genomic information. We discuss suitable software tools and pipelines for marker-based approaches (markers/haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 81 publications
0
43
0
Order By: Relevance
“…The rate of historical genetic gains has indicated that reliance on conventional breeding methods alone is unsustainable to fulfill the need of the burgeoning population (Ray et al, 2012), and we need innovative breeding strategies to accelerate the rate of genetic gains in crop breeding (Barabaschi et al, 2016;Bevan et al, 2017;Xu et al, 2017b). For this reason the scientific community has made heavy investment in developing genomic resources and intelligent decision support systems that would likely reduce the genotype-phenotype gap and provide the effective tools to develop next-generation cultivars (Batley and Edwards, 2016;Varshney et al, 2016). The most commonly applied molecular tools for crop breeding are molecular markers, which are used for parental selection, genetic diversity estimation, and reducing the linkage drags and genomicsassisted breeding.…”
Section: Potential Of Molecular Breeding In Developing Next-generatiomentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of historical genetic gains has indicated that reliance on conventional breeding methods alone is unsustainable to fulfill the need of the burgeoning population (Ray et al, 2012), and we need innovative breeding strategies to accelerate the rate of genetic gains in crop breeding (Barabaschi et al, 2016;Bevan et al, 2017;Xu et al, 2017b). For this reason the scientific community has made heavy investment in developing genomic resources and intelligent decision support systems that would likely reduce the genotype-phenotype gap and provide the effective tools to develop next-generation cultivars (Batley and Edwards, 2016;Varshney et al, 2016). The most commonly applied molecular tools for crop breeding are molecular markers, which are used for parental selection, genetic diversity estimation, and reducing the linkage drags and genomicsassisted breeding.…”
Section: Potential Of Molecular Breeding In Developing Next-generatiomentioning
confidence: 99%
“…This tool comprises six modules including data validation, phenotyping, linkage map building, QTL analysis, genome display, and MABC sample size. Apart from these modules, several other analytical and decision support tools for data analysis software, data storage, and data management will usher crop breeding programs into a modern, knowledge-based crop breeding era, leading to sustainable crop production (Varshney et al, 2016).…”
Section: Genotyping Scenarios and Decision Support Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of analytical and decision support tools for genomics-assisted breeding are freely available [175]. For example, CIMMYT offers several software packages to facilitate various specialized analyses (see.…”
Section: Modern Approaches Technologies and Tools To Support Commermentioning
confidence: 99%
“…Amalgamation of the genomics with the integrated classical breeding has calibre to boost the yield of peanut by overcoming selected genetic barriers. Since a decennary, enormous progress has been made in the peanut genomics leading to the development of enormous genetic and genomic resources such as genome sequences, whole genome re-sequencing (WGRS), molecular markers, mapping populations, genetic maps, high throughput sequencing and genotyping platforms, transcriptome sequencing and proteome (Pandey et al 2012aVarshney et al 2013Varshney et al , 2015a. These resources have been exploited and utilized in genetic map construction, quantitative trait loci (QTL) mapping for traits, association mapping and ultimately transform it in the translational genomics for the improvement of peanut (Pandey et al 2014aVarshney et al 2015b).…”
Section: Introductionmentioning
confidence: 99%